Sosialiasi Pencegahan Penuaan Dini Pada Pekerja Perkebunan Desa Pakis Kecamatan Panti Kabupaten Jember 2022 - Prasetyowati, Irma; Simanjuntak, Tri Damayanti; Bumi, Candra (UPT Penerbitan Universitas Jember, 2023)
Background: Premature Ageing can accelerate the emergence of degenerative diseases. Plantation workers or farmers are a group of workers who are very vulnerable to degenerative diseases and accidents in carrying out their work. This activity aims to socialize the prevention of premature aging among plantation workers. Method: This activity uses the counseling method with the target of plantation workers in Pakis Village, Panti District, Jember Regency. The stages of the activities start from the preparation, implementation, and evaluation of activities. The instrument used is a booklet. Results: The socialization contained definitions of premature aging and emerging degenerative diseases, CERDIK prevention, adherence to using personal protective equipment (PPE) while at work, hand washing with soap (CTPS) behavior, and increased knowledge and behavior paying attention to a healthy and balanced nutritional diet, especially foods that contain antioxidants. Participants actively participate through question and answer. Conclusion: socialization activities to increase the knowledge, understanding, and awareness of plantation workers are crucial to prevent premature aging and degenerative diseases.Keywords: prevention, premature aging, plantation workers